(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the research is to understand the role that Sports has played in the promotion of the education in Kashmir since the outbreak of militancy in 1989. The study focuses on the role played by the JK State Sports council came into existence in 1959 and the Department of Youth Services Sports came into being in the year 1973, prior to the beginning of the militancy in Kashmir.